Influência da taxa de resfriamento no módulo de elasticidade de ligas beta Ti e obtenção de diagramas CCT - Santos, Rafael Formenton Macedo dos (2019)
The metallic alloys used as orthopedic implants, such as the Ti-6Al-4V, present some problems of biological and mechanical compatibility. In addition, the great difference between the elastic modulus of human bone and the commercial alloys used as implants is responsible for the stress-shielding effect. In this way, the objective of this study was to obtain CCT diagrams through dilatometry of β-Ti alloys and to investigate the influence of the cooling rate by comparing the microstructure and properties (microhardness and elastic modulus) for Ti-40Nb (Ti40Nb) and Ti-12Mo-6Zr-2Fe (TMZF) alloys. For this, besides the alloy as received, it was yield the following cooling rates: 103 oC/s for rapidly solidified (SR condition); 102 oC/s for water quenche; 5 oC/s for air cooling and 0.05 oC/s for furnace cooling. Afterwards all the samples were submitted to the microstructural characterization through X-ray diffraction (XRD), optical microscopy (OM) and scanning electron microscopy (SEM). Physical property of elastic modulus E (GPa) was measured via impulse excitation technique while the mechanical property was assessed using Vickers microhardness. Finally, the thermal characterization was performed by differential scanning calorimetry (DSC) and dilatometry. For the SR condition, which showed the lowest values of elastic modulus and Vickers microhardness, the presence of β-Ti (bcc) and α” (martensite) phases for both alloys and the values of modulus and elasticity and Vickers hardness, respectively, with 56 GPa and 144HV for the Ti40Nb (SR), 74GPa and 333HV for the TMZF (SR) alloy. For lowest cooling rate (furnace), the results showed the presence of β and α phases for both alloys, and values of E = 83 GPa and 302 HV for the Ti40Nb alloy and 106 GPa and 443 HV for the TMZF alloy. Based on these results, together with the results of the DSC test and dilatometry, it was possible to build real CCT diagram for both alloys.